2021
DOI: 10.1002/cjoc.202100665
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Synthesis of Polymeric Vesicles with Controllable Size and Low‐Polydispersity by Polymerization‐Induced Self‐Assembly

Abstract: Comprehensive Summary The size and size distribution of polymeric nanoparticles have great impact on their physicochemical and biological properties. Polymerization‐induced self‐assembly (PISA) has been demonstrated to be an efficient method to fabricate various polymeric nanoparticles, among which polymeric vesicles have attracted great interest due to their unique hollow structure. However, polymeric vesicles with relatively broad size distributions and random size are normally formed, which is problematic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Reversible‐deactivation radical polymerization (RDRP) [ 4‐6 ] is a powerful method for precise synthesis of polymers. [ 7‐9 ] In recent years, as enlightened by the importance of MWDs, considerable efforts have been made to regulate MWDs via RDRP (Figure 1a). [ 2 ] For example, the Fors group has carried out systematic studies to tailor the shapes of MWDs, [ 10‐11 ] and revealed their striking impacts on properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Reversible‐deactivation radical polymerization (RDRP) [ 4‐6 ] is a powerful method for precise synthesis of polymers. [ 7‐9 ] In recent years, as enlightened by the importance of MWDs, considerable efforts have been made to regulate MWDs via RDRP (Figure 1a). [ 2 ] For example, the Fors group has carried out systematic studies to tailor the shapes of MWDs, [ 10‐11 ] and revealed their striking impacts on properties.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Recently, the precise preparation of polymers has been central to the development of this discipline. [ 2 ] However, achieving precise control of the main and side chains, as well as the functional groups remains difficult but critical. Additionally, since regulating the geometry of chains, further procedural, and precise control of inter‐ and intra‐chain interactions is the key to the fusion of polymers and supramolecules to achieve future multi‐level precision and intelligent regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Worm‐like micelles are particularly interesting structures due to their highly anisotropic morphologies, which offer diverse applications in material science, such as sterilisable gels for cell culture/storage/transportation, rheology modifiers, nanofiltration, superflocculants, and efficient Pickering emulsifiers [1–6] . Polymerization‐induced self‐assembly (PISA) has been demonstrated to be a powerful strategy for fabrication of various polymeric nanoparticles [7–23] . Compared with the traditional self‐assembly method, efficiently simplified procedures and high solids content are the most notable advantages of PISA [24–40] .…”
Section: Introductionmentioning
confidence: 99%